MODERASI BERAGAMA DAN PENERAPAN AKAD QARDHUL HASAN PADA PRODUK AL-QARDH - Jakfar Shodiq; Nurul Mahmudah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2022)
This study aims to determine the application of the qardhul hasan contract on al-qardh ceria product according to religion moderation. Al-qardh ceria is a benefit financing to finance the productive and consumptive sectors for the poor. This researh uses the type of field research and is descriptive. Data collection uses interviews with information sources from branch leaders, marketing, and members of qardhul hasan financing. The results showed that that the product of al-qardh ceria was not in accordance with Fatwa DSN-MUI No. 19/DSN-MUI/IV/2001. Because in the fatwa, the recipien of al-qardh ceria is only charged an administrative fee. However, in its implementation, members of the qardhul hasan , apart from being charged an administrative fee, memebres are charged a takaful fee.